On sufficient optimality conditions for multiobjective control problems - de Oliveira, Valeriano Antunes [UNESP]; Silva, Geraldo Nunes [UNESP] (Springer Nature, 2016)
This paper is devoted to presenting optimality conditions for the sufficiency of the maximum principle for multiobjective optimal control problems with nonsmooth data. Such conditions are the most general as possible in the sense that problems in which the set of necessary conditions from the maximum principle are also sufficient, necessarily obey them. A variation of such conditions is also presented, under which the set of optimal solutions of the multiobjective problem can be determined by resolving a related scalar weighting problem.
Keywords: Generalized convexity; Multiobjective programming; Optimal control; Optimality conditions